Physical variables - lake profile additional logger system from Erssjön - Skogaryd Research Catchment (University of Gothenburg, 2020)
High frequency additional logger system measurements of CO2 and/or O2 along a depth profile in the lakes of SITES Water.
Skogaryd Research Catchment (2020). Physical variables - lake profile additional logger system from Erssjön, 2019-04-10–2019-12-31 [Data set]. Swedish Infrastructure for Ecosystem Science (SITES). https://hdl.handle.net/11676.1/aCdHCo2c_EGwoRSC0JMA3lRG
Keywords: SITES; Carbon dioxide; Oxygen; Time instant; Time instant; Dissolved oxygen; Dissolved oxygen; Oxygen saturation; Oxygen saturation; Water temperature; Water temperature; Dissolved carbon dioxide; Dissolved carbon dioxide; Carbon dioxide saturation; Carbon dioxide saturation; Soil Science; Markvetenskap; Agriculture, Forestry and Fisheries; Jordbruk, skogsbruk och fiske; Agricultural Science; Jordbruksvetenskap; Ecology; Ekologi; Multidisciplinary Geosciences; Multidisciplinär geovetenskap; Environmental Sciences; Miljövetenskap; Climate Science; Klimatvetenskap